Early warning system in managing water infrastructre projects - Sjekavica Klepo, Mariela; Radujković, Mladen (Journal of Civil Engineering and Management, 2019)
There is a continuous need to improve existing project management decision-making support models, particularly those for monitoring and control are needed to increase chances for success. In this paper, potential of early warning in project management was focused, along with its connection to project success via project success factors. First, a systematic literature review was conducted, along with the focus group method, in order to identify project success factors. The selected success factors were also collected on 93 water infrastructure projects through a survey. By the means of linear regression analysis, critical success factors were finally determined. The results were integrated in the early warning system algorithm, composed by three modules – detection, validation and response module. The response module is composed by three dimensions: 1) risk, constraint and change management, 2) incorporation of project management competences and 3) application of project management methods, tools and techniques. The proposed early warning system was tested on three infrastructure projects. The results confirmed that improved early warning system can contribute in increase of project management success. As original database is composed by projects from only one country (Croatia), in the final stage of the research proposed approach was checked in five countries from the Central or South East Europe (Czech Republic, Slovenia, Serbia, North Macedonia, Bosnia and Herzegovina). The results from the final stage confirmed potential of the proposed approach as declared originally, so it is reasonable to expect success in early warning system’s implementation due to similarities of critical success factors on projects as well as project management problems in general, that countries in regions share. This research presents new and creative way in linking early warning and project success, as well as interpretation of early response through different dimensions in project management. Also, based on the results of this research, it is possible to create a useful practical tool for managing other types of projects.